Evaluasi Pengelolaan Produk Rantai Dingin pada Pedagang Besar Farmasi X Berdasarkan Pedoman CDOB 2020 - Wuri Ariestika Sari; Eri Amalia (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Cold Chain Products are pharmaceutical preparations sensitive to temperature, requiring consistently maintained temperature conditions from production, storage, and transportation to the final consumer. Environmental changes, such as temperature fluctuations and direct sunlight exposure, can reduce product quality, leading to the loss of the product's therapeutic potential. Therefore, Pedagang Besar Farmasi (PBF) play a crucial role throughout the distribution chain of cold chain products to ensure that the quality and effectiveness of the products are maintained. This study aims to evaluate the implementation of cold chain product management at a PBF in Tasikmalaya City according to the applicable guidelines, namely the Good Distribution Practices (CDOB). The study employs observation and interview methods, with evaluation using a research tool in the form of a checklist developed based on aspects of cold chain product management according to the 2020 CDOB guidelines. Based on the evaluation of cold chain product management implementation according to CDOB, a PBF in Tasikmalaya City has successfully implemented CDOB aspects well.